Tension gastrothorax in late-presenting congenital diaphragmatic hernia: a diagnostic dilemma - Sofija Cvejic; Ivana Dasic; Nenad Zdujic; Sanja Sindjic Antunovic; Dejan Nikolic; Polina Pavicevic (The Turkish Journal of Pediatrics)
Background. Tension gastrothorax is a rare life-threatening condition that occurs when the stomach is herniated into the thoracic cavity, most often through the congenital left posterolateral diaphragmatic defect, causing a mediastinal shift when distended with gas and fluid.